Complication of Orthodontic Treatment: A Case Report on Severe Apical Root Resorption (ARR) in a Patient with Turner Syndrome - Joanna Laskowska; Anna Paradowska-Stolarz; Lucía Miralles-Jordá; Dorota Schutty; Marcin Mikulewicz (MDPI AG, 2024)
External apical root resorption in permanent teeth is a multifactorial process influenced by a variety of local and systemic factors. This report describes a case of multiple and severe apical root resorptions in a patient with Turner syndrome. The condition was discovered in a young female with Turner syndrome after 30 months of orthodontic treatment with fixed appliance. The purpose of this report is to present reports by other authors on the potential causes of the increased risk of tooth resorption in patients with Turner syndrome and to share insights derived from its course, highlighting the implications and lessons learned. Patients with Turner syndrome are not ideal candidates for orthodontic treatment. Prior to commencing orthodontic treatment, it is essential to carefully consider the potential benefits of the therapy compared to the risk associated with exacerbating root resorption. In the case of Turner syndrome patients, where there is an elevated risk of such complications, a thorough analysis should be conducted to determine whether the expected benefits of the treatment outweigh the potential hazards to the patient's dental health.